USE OF INFORMATION OF AN ACCOUNTING IN THE MANAGEMENT PROCESS OF AGRIBUSINESSES SANTA MARIA/RS - Strassburger, Rúbia; Talgatti, Maiara; Iensen, Filipe; Guse, Jaqueline Carla; Rossato, Marivane Vestena (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708777 It is a growing need for information that helps administrators in decision making and in their organizational controls. Accounting is a great tool that assists companies in the management process. In view of this, the present study aims to investigate the use of the information generated by accounting in the management process of agribusinesses Santa Maria - RS. To achieve this goal, in addition to literature review, primary data were collected through the use of semi-structured questionnaires to 25 agribusinesses first and second transformation of the municipality. It can be concluded that the companies that own accounting, the majority use the controls and managerial you stand for, and claim that these records are important in decision making.